Thyreotoxische Krise und Myxödemkoma - Milkau, Malte; Sayk, Friedhelm (DMW - Deutsche Medizinische Wochenschrift, 2018)
Thyroid storm and myxedema coma are the most severe clinical forms of thyroid dysfunction. While both hyper- and hypothyroidsm are common diseases, thyroid storm and myxedema coma are rare. Due to their unspecific signs and symptoms they are often difficult to diagnose. Both disorders are medical emergencies, which still show a significant mortality. The following article summarizes diagnostic tools and treatment options for these disorders
Keywords: Thyreotoxische Krise; Myxödemkoma; Funktionsstörungen der Schilddrüse